Enzyme Technology in Value Addition of Wine and Beer Processing - Uzuner, Sibel; Uzuner, Sibel (Elsevier, 2022)
Some endogeneous and exogeneous enzymes participate in the brewery and winery technologies. Industrial enzymes provide quantitative advantages (increased juice yields) and qualitative advantages (enhanced extraction and flavor) for processing (shorter maceration, settling, and filtration time). This review aims to explain the flow process of brewing and wine-making, discuss different enzymes used in brewery and wine-making industry. Also, this chapter summarizes the key enzymes used at different stages of wine-making and brewing, and the challenges of the exogeneous, commercial and immobilized enzymes. Finally, the use of immobilized enzymes is presented as a significant strategy to improve catalyst during brewing and wine-making.
Keywords: Brewing industry; Clarification; Enzymes; Low-caloric beer